PENGARUH UPAH KERJA TERHADAP KINERJA KARYAWAN YANG DIMEDIASI OLEH MASA KERJA DI BIDANG JASA LAUNDRY KABUPATEN BULELENG (STUDI KASUS JASA LAUNDRY DI DESA KAYU PUTIH) - Sudarnaya, Ketut; Sri Nataliani, Luh Putu Desna (Komunitas Manajemen Kompetitif, 2025)
This study aims to examine the effect of wages on employee performance mediated by length of service in the laundry service sector in Kayuputih Village, Sukasada District, Buleleng Regency. This research used a quantitative approach with a sample of 31 employees from various laundry businesses. Data were collected using a questionnaire. The data analysis technique used is Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results show that wages do not have a significant direct effect on employee performance (t = 0.858; p = 0.391). However, wages have a significant effect on length of service (t = 7.345; p = 0.000), and length of service significantly affects employee performance (t = 3.612; p = 0.000). Furthermore, length of service significantly mediates the effect of wages on performance (t = 2.864; p = 0.004), indicating full mediation. The findings conclude that increasing wages helps retain employees for a longer period, which indirectly improves their performance. Therefore, business owners are advised to focus not only on fair wage policies but also on long-term employee retention strategies.